Analisis dan Perancangan User Experience Aplikasi Konferensi Ilmiah menggunakan Metode User-Centered Design - Lendy Seoling; Herman Tolle (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Scientific conference activities are a place for researchers to collect and share their research results. Scientific conference activities are beneficial for the participating participants, where they can get a lot of information about the research methods used to solve a problem. Because there are so many participating writers, reviewers and editors involved, proper management is needed to facilitate all participants in the conference activities. For this reason, it is necessary to design a system that can facilitate the services provided to participants so that they can follow the scientific conference process properly. One of the design methods that can be used is user-centered design. User-centred design is a user-centred design evaluation, focuses on the user and the overall user experience and involves the user throughout the design development process. The results of the design evaluation have been measured using usability testing which focuses on the aspects of effectiveness, efficiency and satisfaction. The results of the effectiveness evaluation get a percentage of 97.8%. The percentage of efficiency is 97.8% and the user satisfaction aspect score is 72.5 and is included in class C which has a high acceptable level.